The conception of stakeholders in managing strategy – case study of the community of Inowrocław - Świerk, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The objective of this article is to present the conception of the stakeholders in managing the organization. The paper discussed the typology of stakeholders and ways of engaging stakeholders in the activities of the organization. Next, the process of determining of stakeholders was analyzed and the proposition of value for stakeholders included in the strategy of community was presented on the example of Inowrocław. In order to obtain implementation and monitoring results of strategy prepared stakeholders perspective dedicated to Balanced Scorecard with measures to monitor the effects of realizing strategy goals.